2017
DOI: 10.3847/1538-4357/aa9a3f
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting Brightness Asymmetries in Transition Disks: Vortex at Dead Zone or Planet-carved Gap Edges?

Abstract: Recent submillimeter observations show nonaxisymmetric brightness distributions with a horseshoe-like morphology for more than a dozen transition disks. The most-accepted explanation for the observed asymmetries is the accumulation of dust in large-scale vortices. Protoplanetary disks' vortices can form by the excitation of Rossby wave instability in the vicinity of a steep pressure gradient, which can develop at the edges of a giant planet-carved gap or at the edges of an accretionally inactive zone. We studi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 118 publications
(164 reference statements)
1
12
0
Order By: Relevance
“…We suggest two ways to distinguish them: First, planet-induced vortices frequently have off-center peaks due to repeated perturbations from the planet's spiral arms. On the contrary, Regály et al (2017) find that without these interactions, vortices at dead zone boundaries remain symmetric even when they have wide azimuthal extents.…”
Section: Confirmation Of Elongated Planet-induced Vorticesmentioning
confidence: 74%
See 1 more Smart Citation
“…We suggest two ways to distinguish them: First, planet-induced vortices frequently have off-center peaks due to repeated perturbations from the planet's spiral arms. On the contrary, Regály et al (2017) find that without these interactions, vortices at dead zone boundaries remain symmetric even when they have wide azimuthal extents.…”
Section: Confirmation Of Elongated Planet-induced Vorticesmentioning
confidence: 74%
“…Second, Regály et al (2017) find that vortices at dead zone boundaries are much more radially-extended than those induced by rapidly-grown planets. In contrast, we have shown that elongated vortices have similar radial extents than concentrated vortices, providing another distinguishing criterion.…”
Section: Confirmation Of Elongated Planet-induced Vorticesmentioning
confidence: 89%
“…We note that the lifetime of a vortex is difficult to predict. There are a number of factors that can reduce the lifetime of vortices, such as the viscosity (de Val-Borro et al 2007;Ataiee et al 2013;Fu et al 2014a;Regály et al 2017), dust feedback (Johansen et al 2004;Inaba & Barge 2006;Lyra et al 2009;Fu et al 2014b), disc self gravity (Regály & Vorobyov 2017a;Pierens & Lin 2018) and the streaming instability (Raettig et al 2015). The lifetimes of vortices formed by giant planets has been investigated and were found to be strongly dependent on planet mass and viscosity, capable of sustaining vortices up to 10 4 orbits in some cases (Fu et al 2014a).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, observations from the near-infrared to millimeter bands in dust continuum and in scattered light have revealed a variety of disk substructures, such as spiral arcs and arms, clumps, rings, and gaps (e.g., van der Marel et al 2013; ALMA Partnership et al 2015;Pérez et al 2016;Liu et al 2016), indicating that protoplanetary disks often do not have simple monotonically declining surface density profiles. Theoretical interpretations of these substructures imply a presence of already-formed massive planets (e.g., Kley & Nelson 2012) or/and physical phenomena at work, such as gravitational instability or vortices, which can assist planet formation (e.g., Dong et al 2016;Regály et al 2017).…”
Section: Introductionmentioning
confidence: 99%